Taxes in an open shop trade union model - Laszlo Goerke (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
In a social custom model of union membership with wage bargaining, higher levels of company taxes lower wages while having uncertain employment effects. A higher marginal income tax rate increases employment. Changes solely in the level of income taxation, retaining marginal rates, have ambiguous wage and employment consequences. Endogenising union membership therefore does not alter the effects of tax changes in comparison to a right-to-manage model with exogenously fixed level of density.
Keywords: A13; H24; H25; J51; 330; Right-to-Manage; Social Custom; Taxes; Trade Union; Verhandlungstheorie des Lohnes; Gewerkschaftsmitgliedschaft; Steuerwirkung; Lohn; Beschäftigungseffekt; Theorie